Digital Transformation and MSME Competitiveness: Strategies for Navigating E-Commerce Competition in the Platform Economy - Nurhasanah Aini (Journal of Emerging Economics and Business, 2026)
The development of the platform economy and the rapid growth of e-commerce have significantly transformed the business competition landscape, particularly for Micro, Small, and Medium Enterprises (MSMEs). This condition requires MSMEs to develop digital-based strategies to maintain competitiveness and business sustainability. This study aims to analyze digital-based MSME strategies in facing e-commerce competition in the era of the platform economy. The research employed a qualitative approach using a library research method. Data were collected from reputable journal articles, academic books, government reports, and publications from international organizations relevant to the research topic. Data analysis was conducted through content analysis involving identification, selection, categorization, interpretation, and synthesis of previous research findings. The results indicate that five key strategies contribute to enhancing MSME competitiveness: digital marketing optimization, digital branding enhancement, customer data utilization, digital payment system integration, and product innovation combined with improved customer service quality. The findings reveal that MSME success in responding to e-commerce competition is determined not merely by technology adoption but by the ability to integrate various digital capabilities into sustainable business strategies. This study contributes conceptually by strengthening the relationship between the platform economy, digital transformation, and MSME competitiveness within an integrated analytical framework.